FAKTOR-FAKTOR YANG MEMPENGARUHI KEJADIAN KANKER PAYUDARA DI RSU DADI KELUARGA PURWOKERTO - Prabandari, Fitria; Fajarsari, Dyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2016)
ABSTRACT: FACTORS AFFECTING THE OCCURRENCE OF BREAST CANCER FAMILY IN RSU DADI PURWOKERTO. Breast cancer is a malignancy derived from glandular cells, duct glands and tissues supporting the breast, not including the skin of the breast. The etiology of breast cancer can not be explained. However, many studies have shown the existence of several factors associated with an increased risk or likelihood of breast cancer. General Hospital Purwokerto Dadi friendly due to an increased incidence of breast cancer from January - October 2014 a number of 2,320 cases of breast cancer. This study uses retrospective case control approach. Analyzed using non-statistical or statistical analysis called sederhana.Untuk test hypotheses about the relationship between two variables used Chi Square. The results of the bivariate analysis will be analyzed using logistic regression for each variable with a value of p <0.25. There is no correlation between age and the incidence of breast cancer in RSU Dadi Family Purwokerto. There is a correlation between the age of menarche with the incidence of breast cancer in RSU Dadi Family Purwokerto. There is a parity relationship with the incidence of breast cancer in RSU Dadi Family Purwokerto. There is a correlation between duration of breastfeeding with breast cancer occurrence in RSU Dadi Family Purwokerto. There is a history of the relationship between hormonal contraceptive use with the incidence of breast cancer in RSU Dadi Family Purwokerto. There is a correlation between a family history of breast cancer with the incidence of breast cancer in RSU Dadi Family Purwokerto. Variables that influence breast cancer incidence are age of menarche, duration of breastfeeding, history of hormonal contraceptive use and family history of breast cancer. Â Keyword: Breast cancer, age, age of menarche, parity, Old Nursing, History of Use Hormonal birth control, the Family History of Breast Cancer